Diversification for Livelihood Security: Experiences from Major Coconut Growing Countries - Kalavathi, S.; Manohar, Erlene; Naka, Peeyanot; Long, Vo Van; Krishnakumar, V.; Thomas, R. J.; Thomas, George V.; George, Maria Luz (International Coconut Community Journal, 2012)
This paper presents the success of community based organizations in achieving sustainability in marginal coconut holdings through diversification of crops and enterprises along with conservation of local varieties. The project was implemented in 19 communities of 10 coconut growing countries and findings from four major coconut growing countries, which had significant project outcome - India, Philippines, Thailand and Vietnam - are discussed in the present paper. All the four major coconut growing countries recorded a significant difference in total household income over the project period. Among the four countries, India and Philippines had a significant difference in mean income derived from intercrops, India and Thailand for livestock integration and India and Vietnam for off-farm activities. Herfindahl index for indicating economic diversity of households revealed a significant diversification of income for India as well as the overall data for the four countries. A higher level of education and more available land also positively influenced total income. In general, improvements in income were better with bigger-sized farms and households, with male household heads. The overall data revealed significant improvement in food and nutritional security with clearest impacts in India and Philippines due to project efforts. Participation of women in trainings and interventions was the highest in India, followed by Thailand.